The Effect of Canal Curvature and Different Manufacturing Processes of Five Different NiTi Rotary Files on Cyclic Fatigue Resistance - Phumpatrakom, Panupat; Klaisiri, Awiruth; Techapatiphandee, Sukitti; Saekow, Thippawan; Aguilar, Panuroot (European Journal of General Dentistry, 2024)
The aim of this study was to evaluate the cyclic fatigue resistance of ProTaper Universal, ProTaper Next, E-FLEX EDGE, E-FLEX ONE, and ZenFlex nickel-titanium (NiTi) rotary files in 60 and 90 degrees of simulated canal curvature.ProTaper Universal, ProTaper Next, E-FLEX EDGE, E-FLEX ONE, and ZenFlex were used in this study. Each system was divided into two groups testing in simulated canals with 60 and 90 degrees of curvature. Both groups were set to rotate under a controlled temperature at 37°C until fracture. The number of cycles to fracture (NCF) was recorded and two fractured files from each group were randomly selected to analyze the fractographic pattern using scanning electron microscopy (SEM).The NCF between the two groups was analyzed statistically using the Mann–Whitney U test. The statistical differences between each system at the same degree of artificial canal curvature were analyzed using the Kruskal–Wallis test. A significant difference was set at p < 0.05.E-FLEX ONE showed the highest mean NCF (p < 0.05) when performed in 60- and 90-degree curvatures. In addition, the file tested in a 60-degree curvature exhibited higher resistance to cyclic fatigue than the one tested in a 90-degree curvature in the mutual NiTi system (p < 0.05). The SEM micrographs exhibited a similar crack initiation area, which is the feature of cyclic fatigue failure.E-FLEX ONE showed the greatest resistance to cyclic fatigue in both 60 and 90 degrees of curvature. This study implies that E-FLEX ONE is appropriate for severely curved canals.
Keywords: blue heat–treated; cyclic fatigue resistance; martensitic composition; metallurgical process; nickel-titanium rotary file